Is bioethics a science? - Ortiz Millán, Gustavo (Estudios de Filosofía, 2022)
This article enquiries whether normative bioethics can be a science. The article aims to address the conditions of possibility for bioethics to be considered a science, without directly answering the question. The article focuses on two conditions that we typically associate with our common concept of science: truth and knowledge, on the one hand, and naturalization, on the other. Bioethics should be able to provide moral truths and therefore moral knowledge so that we could consider it as a science. On the other hand, the normative character of bioethics raises the question of whether it is possible to naturalize it and make it compatible with a scientific perspective. The article argues that, for normative bioethics to be considered a science, a cognitive and naturalistic stance should be taken on ethics.